2014
DOI: 10.1051/0004-6361/201323270
|View full text |Cite
|
Sign up to set email alerts
|

Planck intermediate results

Abstract: The dust-H i correlation is used to characterize the emission properties of dust in the diffuse interstellar medium (ISM) from far infrared wavelengths to microwave frequencies. The field of this investigation encompasses the part of the southern sky best suited to study the cosmic infrared and microwave backgrounds. We cross-correlate sky maps from Planck, the Wilkinson Microwave Anisotropy Probe (WMAP), and the diffuse infrared background experiment (DIRBE), at 17 frequencies from 23 to 3000 GHz, with the Pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 139 publications
(11 citation statements)
references
References 82 publications
2
9
0
Order By: Relevance
“…This trend is similar to what is found in the case of high-latitude clouds (Paper I). Recent studies by the Planck Collaboration have also found that T d increases with decreasing gas column density (Planck Collaboration et al 2014a, 2014b. By following the same argument as in Paper I, we expect that the H i emission is moderately optically thick in general and that the saturation due to the optical depth effect causes weaker W H i for lower T d and higher τ 353 .…”
Section: Tablesupporting
confidence: 62%
“…This trend is similar to what is found in the case of high-latitude clouds (Paper I). Recent studies by the Planck Collaboration have also found that T d increases with decreasing gas column density (Planck Collaboration et al 2014a, 2014b. By following the same argument as in Paper I, we expect that the H i emission is moderately optically thick in general and that the saturation due to the optical depth effect causes weaker W H i for lower T d and higher τ 353 .…”
Section: Tablesupporting
confidence: 62%
“…We thus tested our assumption by measuring the β d of the dust total intensity in the BICEP2/Keck field using the template fitting analysis described in Ref. [44], and find the same value.…”
Section: B Fiducial Analysismentioning
confidence: 94%
“…In the local ISM, Grenier et al (2005b) have shown that the use of H I, CO, and a dust residual map improves the fits to the interstellar γ-ray emission compared to using the sole dust map for the total gas. While the hydrogen is likely to have the same γ-ray emissivity per atom in the atomic, DNM, and molecular components of the ISM due to the good penetration of CRs at the GeV-TeV energies relevant for the LAT (Skilling & Strong 1976), dust opacity (optical depth per gas nucleon) is known to increase from the diffuse H I to dense H I and H 2 gas (Stepnik et al 2003;Abergel et al 2013Abergel et al , 2014Ade et al 2014b). Restricting the use of dust to tracing the DNM alleviates the impact of dust opacity gradients because the DNM spans a moderate range of gas volume densities and is rather diffuse in space.…”
Section: Dark Neutral Mediummentioning
confidence: 99%